D4F alleviates macrophage-derived foam cell apoptosis by inhibiting the NF-κB-dependent Fas/FasL pathway - Hua Tian (Nature Portfolio, 2017)
Abstract This study was designed to explore the protective effect of D4F, an apolipoprotein A-I mimetic peptide, on nuclear factor-κB (NF-κB)-dependent Fas/Fas ligand (FasL) pathway-mediated apoptosis in macrophages induced by oxidized low-density lipoprotein (ox-LDL). Our results showed that ox-LDL induced apoptosis, NF-κB P65 nuclear translocation and the upregulation of Fas/FasL pathway-related proteins, including Fas, FasL, Fas-associated death domain proteins (FADD), caspase-8 and caspase-3 in RAW264.7 macrophages, whereas silencing of Fas blocked ox-LDL-induced macrophage apoptosis. Furthermore, silencing of P65 attenuated macrophage apoptosis and the upregulation of Fas caused by ox-LDL, whereas P65 expression was not significantly affected by treatment with Fas siRNA. D4F attenuated the reduction of cell viability and the increase in lactate dehydrogenase leakage and apoptosis. Additionally, D4F inhibited ox-LDL-induced P65 nuclear translocation and upregulation of Fas/FasL pathway-related proteins in RAW264.7 cells and in atherosclerotic lesions of apoE−/− mice. However, Jo2, a Fas-activating monoclonal antibody, reversed the inhibitory effect of D4F on ox-LDL-induced cell apoptosis and upregulation of Fas, FasL and FADD. These data indicate that NF-κB mediates Fas/FasL pathway activation and apoptosis in macrophages induced by ox-LDL and that D4F protects macrophages from ox-LDL-induced apoptosis by suppressing the activation of NF-κB and the Fas/FasL pathway.